Cara Gila Jatuh Cinta: Analisa Qasidah dan Muqataat Mansur Al-Hallaj - Miswari, Miswari (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2019)
This paper aims to analyze the songs of love revealed by Al-Hallaj in Qadisah and Muqattaat. The two titles are a set of Al-Hallaj sufistic love songs that have been collected and published by Louis Massignon, a French orientalist who dedicated a large part of his life to studying Al-Hallaj texts. The author uses relevant references in analyzing Al-Hallaj songs. The search results show that Al-Hallaj's teachings which are far from being rational on the surface turned out to contain meaningful wisdom. Al-Hallaj shows, only with the search for entitlement into self, then the Absolute Reality called Al-Haqq can be found, realized and believed to be the only True Reality.